l-Cystine-Based Polyurethane as a Drug-Delivery Vehicle in Targeted Cancer Therapy and Biomedical Applications - Bauri S.; Yadav P.K.; Choudhury A.M.; Maiti P. (My University, 2025)
Controlled and sustained drug release is a critical aspect of drug-delivery systems (DDSs) that can be used in chemotherapy while ensuring therapy effectiveness and biosafety. Hence, polyurethane (PU) is modified using a biomolecule Cystine (CYS) for protracted drug release, aiming to enhance cancer treatment efficacy while minimizing adverse side effects in tumor patients. To confirm the formation of a polymer structure, characterization techniques such as NMR and FTIR are used, and the morphology is determined using SEM. Biocompatibility of the synthesized polymers is evaluated through cellular assessments, including MTT assay, cell adhesion, and antibacterial assay along with drug release using an anticancer drug, Paclitaxel (PTX). Notably, the incorporation of PTX in the polymer matrix results in minimal mortality (85% viable cells) rates in healthy cells (3T3), in contrast to a 56% mortality rate observed with the pure drug. While PTX shows a burst release and kills cancer cells only for the first 24 h, PU loaded with the drug shows sustained release and kills the cancer cells for 3 days. This vehicle selectively kills 59% of SiHA cells after a consecutive study of 3 days, which highlights the potential of this newly designed vehicle for effective drug delivery, particularly in anticancer treatments. Moreover, cystine’s antibacterial property adds up with PU; hence, PU shows antibacterial activity against Staphylococcus aureus (MIC, 20 μg/mL) and also acts as a reductive oxygen species scavenger. Therefore, modifying PU with CYS has shown sustained release of PTX along with a selective effect on cells, underscoring its significance as a superior delivery agent and supported by a shred of convincing evidence. © 2024 American Chemical Society.